Leukemia Inhibitory Factor Decreases the Arylamine N-Acetyltransferase Activity in Human Cumulus Granulosa Cells - Chang, Chi-Chen (Kluwer Academic Publishers-Plenum Publishers, 2001)
Purpose: To evaluate the activities of acetyl coenzyme A (AcCoA): arylamine N-acetyltransferase (NAT) of intact cumulus granulosa cells and the role of leukemia inhibitory factor (LIF) upon their NAT activities. Methods: Thirty women accepted controlled ovarian hyperstimulation (COH) and oocyte retrievals. Human cumulus granulosa cells were obtained during oocyte retrievals. Using 2-aminofluorene (2-AF) and p-aminobenzoic acid (PABA) as substrates, NAT activity of all samples was determined by high pressure liquid chromatography. After the incubation with different time and concentrations of 2-AF, PABA, and LIF, 2-acetyl-aminofluorene (2-AAF) and N-acetyl-PABA (N-Ac-PABA) were measured. Results: After incubation with 2.812, 5.625, 11.25, and 22.5 μM of 2-AF/PABA, their product concentrations (2-AAF/N-Ac-PABA) were 0.42/0.32, 0.76/0.58, 1.29/1.04, and 1.94/1.26 nmol/10(6) cells, respectively. After 6, 12, 18, and 24 h incubation with 11.25 μM of 2-AF/PABA, their product concentrations were 0.19/0.12, 0.56/0.4, 0.98/0.79, and 1.3/1.0 nmol/10(6) cells, respectively. After incubation with 0, 5, and 50 μM of LIF, the 2-AAF/N-Ac-PABA concentrations were 0.98/0.80, 0.70/0.52, and 0.49/0.30 nmol/10(6) cells, respectively. Conclusion: Intact human cumulus granulosa cells could acetylate arylamine carcinogen (2-AF) and noncarcinogens drug (PABA). LIF decreased the NAT activities. It provides a model for monitoring the effects of COH and LIF upon the oocytes.